2011
DOI: 10.1111/j.1528-1167.2010.02940.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short‐ versus long‐term ketogenic diet for intractable infantile spasms

Abstract: SUMMARYPurpose: To compare the prognoses between short-term (8 months) and conventional long-term (>2 years) trials involving patients with refractory infantile spasms who successfully completed the ketogenic diet (KD). Methods: Of 40 patients who achieved seizure-free outcomes and showed improvement in hypsarrhythmic patterns within 6 months of the KD, with a 3:1 fat to nonfat ratio as an add-on treatment, 16 patients were randomized into the short-term trial group and the diet was tapered throughout two addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…However, there is evidence that they may tolerate a reduced ratio (with increased carbohydrate intake) in a longer term. In the case of IS, a study randomizing the seizure-free patients to either discontinue the diet in the short-term (8 months) or long term (2 years) showed no difference in the rate of seizure relapse between the two groups [58]. Considering the possible occurrence of side effects including growth consequences, a shorter duration of KD in IS might be considered.…”
Section: Discontinuationmentioning
confidence: 99%
“…However, there is evidence that they may tolerate a reduced ratio (with increased carbohydrate intake) in a longer term. In the case of IS, a study randomizing the seizure-free patients to either discontinue the diet in the short-term (8 months) or long term (2 years) showed no difference in the rate of seizure relapse between the two groups [58]. Considering the possible occurrence of side effects including growth consequences, a shorter duration of KD in IS might be considered.…”
Section: Discontinuationmentioning
confidence: 99%
“…Class 4 evidence supports the role of the ketogenic diet for infants younger than 1 year of age, and class 3 evidence for children aged 12-24 months. [12][13][14][15][16][17][18][19][20] There is evidence that ketosis can be sustained in infants.…”
Section: Approach To Therapy and Interventions In Infantile-onset Seimentioning
confidence: 99%
“…Lastly, even though the study from Sweden suggested that carotid stiffness may improve after 12 months of dietary therapy, it would seem logical, based on the Italian results, to consider diet discontinuation at 1-2 years if medically indicated to allow blood vessels to normalize. For some conditions such as infantile spasms, 6 months only of dietary therapy may be sufficient (8).…”
Section: Danger In the Pipeline For The Ketogenic Diet?mentioning
confidence: 99%